Metabolic rearrangements in grapevine response to salt stress - Conde, Artur (2016)
Saline soils make up 20% of the world's cultivated soils and are a serious management issue for irrigated crops in semi-arid regions. Grapevines are considered moderately sensitive to salinity. Although they are particularly sensitive to chloride, different rootstocks can provide important chloride exclusion properties to the scion. Several approaches to grow Vitis vinifera plants more stress-tolerant may include the improvement of cultural practices, the selection of more tolerant cultivars and the production of Vitis hybrids. Increasing knowledge of the metabolic rearrangements involved in the response to an environmental stress such as high soil salinity, but also to drought or heat, could open the possibility of better adapted vineyard management (exogenous compounds, canopy control, etc.) without necessarily turning to genetic manipulation.